2018
DOI: 10.1097/md.0000000000011723
|View full text |Cite
|
Sign up to set email alerts
|

Massive retroperitoneal hematoma following colonoscopy

Abstract: Rationale:Colonoscopy has been used for screening and treatment of diseases worldwide. Endoscopic mucosal resection (EMR) has many major complications such as colon perforation and bleeding. However, cases of minor complications have also been reported. Here, we present a case of massive retroperitoneal hematoma, as a minor complication, after colonoscopy.Patient concerns:A 57-year-old man was admitted to our hospital because of abdominal pain. He had no past medical history relating to his present condition, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…The risk of these AEs is reported predominantly in elderly population, patients with comorbidities, and those who undergo polypectomy and endoscopic mucosal resection [ 2 , 3 ]. Potentially life-threatening AEs like pericolonic hematoma and massive retroperitoneal hematoma may also occur, and there is scant literature published on these rarer AEs [ 4 , 5 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The risk of these AEs is reported predominantly in elderly population, patients with comorbidities, and those who undergo polypectomy and endoscopic mucosal resection [ 2 , 3 ]. Potentially life-threatening AEs like pericolonic hematoma and massive retroperitoneal hematoma may also occur, and there is scant literature published on these rarer AEs [ 4 , 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a 2016 evidence synthesis report by Agency of Healthcare Research and Policy, the authors reported the overall rate of major bleeding of 0.8 per 1,000 procedures (n Z 3,347,101, 95% CI, 0.5–1.4) and the perforation rate of 0.4 per 1,000 procedures (95% CI, 0.2–0.5) for screening colonoscopy [ 3 ]. Globally, most studies of AEs of this procedure are conducted in the West and relatively few studies have been conducted in the East [ 4 , 6 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation